Consumption tax on plastic bags: Analysis of its application in three supermarkets, Puno region, 2021 - Quispe Baca, Liz Danitza (2022)
The objective of this research was to analyze the perception of three supermarkets before the application of the tax on the consumption of plastic bags, considering that their exaggerated use is the cause of environmental deterioration. The applied methodology had a focus on qualitative, exploratory, phenomenological, the design fits are non-probabilistic for convenience, based on experiences of three taxes specialist supermarkets, using semi-structured interviews as an instrument. As a result of the analysis of interviews conducted before the modification of the norm of the consumption tax on plastic bags (ICBP), on tax issues and the effectiveness, there are shortcomings; because only a small sector has been fulfilled, there are also many limitations due to informality since the law was established N.° 30884, it can be seen that there is a significant reduction consumption of single-use plastic bags. Secondly, supermarkets in the Puno region have been applying environmentally friendly alternatives to mitigating pollution and offering customers biodegradable bags, on the other hand, the other supermarkets are implementing these measures, therefore it is concluded that this law, as a mechanism to reduce pollution, if its main purpose of mitigating the use of plastic bags of single-use, but not get monetary resources (collect).